2016
DOI: 10.4236/ajmb.2016.64014
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of DNA Barcode-Based Delineation Using Seven Putative Candidate Loci of the Plastid Region in Inferring Molecular Diversity of Cowpea at Sub-Species Level

Abstract: The novelty and suitability of the mitochondrial gene CO1 in DNA barcoding as a reliable identification tool in animal species are undisputed. This is attributed to its standardized sequencing segment of the mitochondrial cytochrome c oxidase-1 gene (CO1) which has the necessary universality and variability making it a generally acceptable barcode region. CO1 is a haploid single locus that is uniparentally-inherited. Protein-coding regions are present in high-copy numbers making it an ideal barcode. The mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These results indicated that multi-region sampling can improve the resolution of the analysis. In addition, two protein-coding genes (rpoB and rbcL), which were considered as having a high level of variability in angiosperms, have been recommended and used for phylogenetic studies (Chase et al 2007;Okoth et al 2016;Uchoi et al 2016;Sha et al 2017;Oyebanji et al 2020). They were also used for understanding the phylogenetic relationships and diversity in subgenus Cerasus (Jung and Oh.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that multi-region sampling can improve the resolution of the analysis. In addition, two protein-coding genes (rpoB and rbcL), which were considered as having a high level of variability in angiosperms, have been recommended and used for phylogenetic studies (Chase et al 2007;Okoth et al 2016;Uchoi et al 2016;Sha et al 2017;Oyebanji et al 2020). They were also used for understanding the phylogenetic relationships and diversity in subgenus Cerasus (Jung and Oh.…”
Section: Discussionmentioning
confidence: 99%
“…For the mutations of sequences, the single nucleotide polymorphism (SNP) and deletion or insertion (InDels) of nucleotide bases are the most common variations in the sequences of plastome (Decesare, Hodkinson & Barth, 2010;Kim et al, 2015). These variations have provided ideal information for developing polymorphic markers for numerous applications such as molecular barcoding (Okoth et al, 2016;Zong et al, 2019), phylogenetic reconstruction (Peterson, Romaschenko & Johnson, 2010), biogeographic studies (Kress et al, 2009;Xie et al, 2019), assessment of the maternal line of hybrid species (Schroeder, Höltken & Fladung, 2011;Tomar et al, 2014;Chung et al, 2019), and clarification of the evolutionary relationship between cultivated and crop wild relatives (Gao et al, 2019). Currently, with the advancement of next-generation sequencing technologies (NGS), sequencing of chloroplast genomes and the development of plastid genetic markers have become feasible in various plant genetic researches (Brozynska, Furtado & Henry, 2014;Bi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of cp-DNA microsatellites in the chloroplast genome has been widely utilized for delineating and reconstruction of phylogenetic relationships, taxonomic studies and the identification of maternal patterns in polyploids. The National Gene Bank of Kenya holds a repository of cowpea accessions from diverse phylogeographic backgrounds [1]. They carry a repertoire of genetic diversity, not adequately characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, it is possible to detect subtle anatomical variations associated with small fitness effects that can account for genetic diversity at varietal level. The lack of sequence information in Kenyan cowpea has limited the robust advancement of molecular markers use in dissecting diversity based on the putative plastid markers [1]. The present study sought to generate and upscale novel technologies such as genomics, DNA barcoding and bio-informatics in understanding molecular diversity of cowpea acces-…”
mentioning
confidence: 99%